Seeing red: pearls for vascular laser treatment (Canadian Dermatology Today, 2022)
Dermatologists diagnose vascular lesions routinely in clinical practice. Many such lesions are benign neoplasms (e.g. cherry angiomas, venous lakes), while others occur in the setting of a dermatological condition (e.g. rosacea) that can be managed in part with an existing medical toolbox of treatment options. While some patients are reassured once a benign diagnosis has been established, some may seek elective treatment of these lesions. As dermatologists, we are in position to provide safe and effective elective treatment with various physical modalities. Vascular lasers are a group of devices that can target hemoglobin as a chromophore, providing treatment selectivity and the potential for scarless outcomes. This article aims to share practical pearls for the optimization of vascular laser treatments in clinical practice.